Anthropomorphism of the Character Kitsune in Mukashi Banashi - Linda Unsriana; Felita Euginia (IZUMI, 2024)
Japanese folktales (mukashi banashi) have many characters that are animals or non-living things acting as if they are humans, such as racoons (tanuki) that can talk, birds that can dance, or even persimmons and cow’s feces that can talk. One of the most famous animals in Japanese folklore that behave like humans is the kitsune. Kitsune are also depicted as characters that are wicked or evil, and at other times, they are depicted as being good. The purpose of this research is to find out the anthropomorphism of kitsune characters and whether they are depicted as good or evil in mukashi banashi. This research uses a library research method that is done qualitatively. This research also analyzes dialogues and narratives in chosen mukashi banashi, with the theory of anthropomorphism, taken from mukashi banashi websites Gongitsune, Sanboneda no Kamisori Kitsune, and Bakekurabe. This research has found that: (2) Kitsune act, talk, have human feelings, and even know human culture; (2) Kitsune are characters that are morally ambiguous. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor